Oxidation of aniline using different reaction pathways - Turhan, Kadir; Uzman, Sueheyla (ASIAN JOURNAL OF CHEMISTRY, 2008)
The goal of this study is to cleavage of aromatic ring of aniline to minimize its hazardous environmental effects. Therefore a method has been developed to remove aniline using potassium dichromate as an oxidizing agent. In the beginning of the study, chemical oxygen demand (COD) experiment was chosen as a test method to oxidize aniline. Titration part of COD experiment was replaced by UV measurement. Cerium(IV) sulfate was also used as an alternative oxidizing agent in COD experiment. As a follow-up work, experimental conditions as reported in the literature for aniline oxidation to p-benzoquinone were modified. Oxidation agents mentioned above lack the strength to oxidize aniline until ring opening. Therefore, ozone was used as an oxidizing agent to break down the aromatic ring of aniline in the second part of the study. In the reaction with ozone, performed at pH 9, it was observed that CO2 and H2O formed through nitrobenzene, azobenzene, azoxybenzene and 2-pyridine carboxylic acid depending on ozone concentration, reaction time and bubble size of ozone. As a conclusion, ozone was excellent oxidant among the investigated three oxidant (K2Cr2O7, Ce(SO4)(2) and ozone) to cleavage of aniline ring to non-hazardous compounds.
Keywords: aniline; oxidation; environmental pollutant; ozonization; advanced oxidation processes; OZONE; Chemistry